The Political Scene In The Gulf Countries Before The Events Of September 11, 2001 - Mohammed Amin, Rafid Ahmed (Opción, 2019)
The end of the Second Gulf War, the liberation of Kuwait, the removal of the Iraqi army from it, and the return of the legitimate government to the capital of Kuwait were not the end of the political and security instability in the Arab Gulf states, but the consequences of the security situation extended beyond and beyond, as it reflected on the Gulf-regional relations, as well as Destroy- ing the infrastructure of Iraq and Kuwait and draining large sums of imports from Arab countries in the Arabian Gulf. Despite the traditional character of the Kuwait crisis, the United States planned to contain the region in anticipation of the potential security threats ahead to secure energy supplies first and devote its influence second, in the sense of controlling the region’s capabilities and absolute control to the extent that it does not need any future international cover as it was keen to secure this cover in the Gulf War In 1991, the United States acted in the context of its presence in the region to act unilaterally to counter potential and perceived threats to US interests in the Gulf region.